2009
DOI: 10.1126/science.1178258
|View full text |Cite
|
Sign up to set email alerts
|

Hemagglutinin Receptor Binding Avidity Drives Influenza A Virus Antigenic Drift

Abstract: Rapid antigenic evolution in the influenza A virus hemagglutinin precludes effective vaccination with existing vaccines. To understand this phenomenon, we passaged virus in mice immunized with influenza. Neutralizing antibodies selected mutants with single amino acid hemagglutinin substitutions that increased virus binding to cell surface glycan receptors. Passaging these high avidity-binding mutants in naïve mice, but not immune mice, selected for additional hemagglutinin substitutions that decreased cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
490
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 445 publications
(522 citation statements)
references
References 17 publications
29
490
1
2
Order By: Relevance
“…However, our results also showed that nucleotide substitutions can occur in the signal peptide and the HA2 region of the HA, which were not evaluated by Murcia et al (2012). In addition, other factors in our study, such as the group housing conditions, which facilitated greater interaction between pigs compared with previous studies where pairs of individuals were used to measure intra-host diversity of IAV (Hensley et al, 2009;Murcia et al, 2010Murcia et al, , 2012, may have had an effect on the increased overall genetic diversity.…”
Section: Discussioncontrasting
confidence: 50%
“…However, our results also showed that nucleotide substitutions can occur in the signal peptide and the HA2 region of the HA, which were not evaluated by Murcia et al (2012). In addition, other factors in our study, such as the group housing conditions, which facilitated greater interaction between pigs compared with previous studies where pairs of individuals were used to measure intra-host diversity of IAV (Hensley et al, 2009;Murcia et al, 2010Murcia et al, , 2012, may have had an effect on the increased overall genetic diversity.…”
Section: Discussioncontrasting
confidence: 50%
“…However, we urge caution in these interpretations, as our understanding of the selective forces on HA and NA is still limited. While much attention has focused on the selection of mutations in known HA antibody epitopes, other regions of HA and NA may contribute to viral fitness through glycosylation [36], compensatory or epistatic interactions [37] or increased avidity for host cell receptors [38]. Further, adaptive evolution, even when not directly driven by humoural immunity, may be more commonly tolerated on macromolecular surfaces owing to stronger structural constraints on internal residues [39].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to circulating seasonal strains, natural IAV infections in zoonotic reservoirs undergo antigenic drift (12,13) and antigenic shift (19) that efficiently evade host immune responses and cause extensive morbidity when transmitted to humans. Complications associated with swine (H1N1) and avian (H5N1, H7N9) IAV infection includes inflammation of the airways, epithelial necrosis, edema, hemorrhaging, and respiratory failure (8,29,44).…”
mentioning
confidence: 99%